Prophylaxis of Community-Acquired Pneumonia Outbreaks with Pneumococcal Polysaccharide Vaccine. Prospects Analysis for Russian Military Community - I. A. Guchev; O. I. Klochkov; A. I. Sinopalnikov (Антибиотики и Химиотерапия)
Pneumococcal pneumonia and other diseases caused by pneumococci still remain the main factors of high morbidity and mortality rates throughout the world. Pneumococci as the leading pathogens of community-acquired pneumonia (CAP), acute otitis media and sinusitis also cause a number of other serious systemic disorders including invasive infections with high mortality in spite of the antimicrobial resistance status and adequate antimicrobials choice. Pneumococcal infections are responsible for 5-35% or more of community-acquired pneumonias. The burden of pneumonia (up to 100-200%) is recorded among military recruits in training centers. Since the specific environment of the soldiers could be carrected, their health protection requires medical surveillance. For these reasons, polysaccharide and more immunogenic conjugated pneumococcal vaccines were developed. There is now an urgent need to understand whether such vaccines are effective in military conscripts. Controversy about the effectiveness and value of the polysaccharide (PPV-23) vaccine as a CAP morbidity restriction measure still persists. There were implemented plenty of metaanalyses of pneumococcal vaccines in adults. Some of them showed that the vaccine was effective against bacteremic pneumococcal pneumonia in 'low risk' healthy adults and elders. There have been a number of poor quality observational studies in Russia where 'all pneumonia cases' were considered as an endpoint. It remains controversial whether these observational studies provide adequate evidence to justify the use of the polysaccharide vaccine in the groups of healthy young men for whom it is being advocated. In our analysis we found weak evidence supporting pneumococcal vaccination with PPV-23 for this group. Nevertheless, favorable tendency was found to immunize. It is the reason for a trail to find pharmacoepidemiological support for vaccination by novel conjugated vaccines with better immunogenicity.